Inorganic Chemistry in Latin America. Issue 5 (7th January 2021) - Castillo, Ivan; Fadini, Luca; Doctorovich, Fabio; Rossi, Liane M.; González‐Gallardo, Sandra
Abstract: The European Journal of Inorganic Chemistry takes pride in showcasing the high‐quality research produced by some of the currently most active scientists in Latin America. With this initiative, we seek to highlight the breadth and depth of the science developed in the region, and to enhance its visibility in the wider chemistry community. Abstract : Growing and glowing : The European Journal of Inorganic Chemistry takes pride in showcasing the high‐quality research produced by some of the currently most active scientists in Latin America. With this initiative, we seek to highlight the breadth and depth of the science developed in the region, and to enhance its visibility in the wider chemistry community.